Fruiting phenology in Aspidosperma discolor and implications for seed dispersal and population distribution - Menezes, Isiara Silva; dos Santos, Marília Grazielly Mendes; Cerqueira, Carlianne Oliveira; do Couto-Santos, Ana Paula Lima; Paula Santos Neves, Sâmia; Rossatto, Davi Rodrigo [UNESP]; de Miranda, Lia dAfonsêca Pedreira; Funch, Ligia Silveira (FapUNIFESP (SciELO), 2024)
We investigated Aspidospermadiscolorfruiting in three subpopulations in the inland Atlantic Forest of Northeastern Brazil, to better understand how local and global factors (such as the El Niño Southern Oscillation - ENSO) drive fruiting, and how functional traits are related to its dispersal potential and spatial distribution. Observations of mature fruits with dispersing seeds were carried out between 1993 and 2012. Dispersal potential was evaluated using seeds released at two different heights. Spatial distribution was analyzed using the Standardized Morisita dispersal index. A. discolor displayed seasonal fruiting during the dry season in all subpopulations, with variations in their average dates but without significant interannual variations in the proportions of fruiting individuals. The undulate seeds had average dispersal distances between 57.36 and 79.54 m. We found a random distribution pattern of the trees. The seasonal dry/rainy regime influenced fruiting and dispersal patterns, and seeds were released during the dry season (even in ENSO years). So, we demonstrate the importance of wind dispersal as a driving factor of fruiting, associated with an abiotic filter (low humidity) during the dry season. Additionally, the aerodynamic nature of the undulate diaspore and its dispersal potential influenced the random pattern of spatial distribution of A. discolor.
Keywords: anemochoric seeds; seasonality; spatial distribution; tropical forest